Centralsystem för informationsskärmar - Bandgren, Robin; Engström, Viktor (My University, 2015)
The information display industry is still growing and the demand is constantly growing. However, when it comes to the possibility to be able to switch between internal company news or lunch menus, to information about ongoing alarms in a building, or production process, the market is unexplored. The project aims to solve that issue and to make it possible for information displays to quickly switch between regular everyday information to a, for example, fire alarm information image, with information about where the alarm is and the fire escape routes. The solution is to automatically get images or files that are to be displayed on the screens from folders on a server unit and upload them in to a webpage. If an alarm would go off in the system the process supervising program will upload information in to a higher priority folder. From there the information display system will get the information and put it up on the display, and in the same instance remove the regular information slideshow. The information screen is possible to open in a regular web browser or in smart-products like a phone or TV through an application.
Keywords: Data- och informationsvetenskap; Computer and Information Science